RISK ASSESMENT AND DISTRIBUTION MODELLING OF INVASIVE SPECIES IN PAPANDAYAN MOUNTAIN NATURE RESERVE, WEST JAVA - Sella Nyuanti, Anggi
Papandayan Mountain Nature Reserve is a region that often experiences various natural disasters, such as anthropogenic disturbances in the form of forest encroachment, opening up the environment to be more vulnerable, as well as volcanic eruptions. This condition proves to be a suitable environment for the growth of invasive species. The presence of invasive species frequently results in negative impacts towards the environment, the economy and health of humans and animals. Several efforts in controlling invasive species have been implemented: mechanically, chemical, or through biological. However, the results of these methods have been deemed ineffective. The effectiveness of controlling invasive species needs to be supported by the availability of basic data on species diversity, risk level, and spatial distribution of invasive species. This research aims to identify the invasive species in Papandayan Nature Reserve, that must be prioritized to managed by analyze the risk of invasive species and modeling the presence of invasive species using Maximum Entropy (MaxEnt). Data on species diversity was collected by vegetation analysis was conducted to determine the invasive species, using the quadratic method. This was done by purposively sampling plots on three types of land cover, i.e. moor, crater rim, and mixed forest. Then an invasive species risk assessment was carried out using scoring method for invasive potential by assessing invasiveness, impact, distribution potential and management feasibility by assessing cost control, distribution, and persistence. After determining which species that will be prioritized, its followed by modeling the distribution of the invasive species. The Maxent model was run using the presence-only data of an invasive species with the highest risk and seven environmental variables, i.e. elevation, slope, aspect, vegetation index (normalized difference vegetation index), moisture index (normalized difference moisture index), landcover and the distance to road. Results showed the existence of six invasive species, i.e. Ageratina riparia, Ageratina adenophora, Austroeupatorium inulifolium, Imperata cylindrica, Rubus mollucanus and Ageratum conyzoides. Based on risk assessment, A. riparia will need to be managed in the highest priority in Papandayan, due to it having the highest risk of invasiveness (154.22), with low feasibility of control (182.21). The results of Maxent modelling of A. riparia shown that slope and elevation are the most important variables for A. riparia distribution. This species tends to distribute in the areas with elevation range of 2200-2375 masl and slope less than 15°. About 94 ha area in the central part of Papandayan Nature Reserve are suitable for A. riparia habitat.